Do male-derived substances affect female mating receptivity and release of sex pheromone by females of the sorghum plant bug Stenotus rubrovittatus (Hemiptera: Miridae)? - Keiko OKU; Takashi YAMANE (European Journal of Entomology, 2014)
In insects, male-derived substances transferred during copulation often alter female physiology. Thus these substances may affect female behaviour, including mating receptivity and release of sex pheromone. In the sorghum plant bug Stenotus rubrovittatus (Matsumura) (Hemiptera: Miridae), males transfer a spermatophore into the bursa copulatrix of females during copulation. Mated females of S. rubrovittatus do not mate again for at least 3 days and release lower amounts of sex pheromone than virgin females. A previous study indicates that females that receive a spermatophore are less likely to be sexually receptive to males. Therefore, we tested whether an extract of the male reproductive organ affected female mating receptivity and whether this extract and spermatophores per se affected the release of sex pheromone by females. The mating receptivity of virgin females injected with an extract of male reproductive organs was significantly lower than that of control females injected with distilled water, but not significantly different from that of females injected with an extract of male thorax (the negative control). The amount of sex pheromone released by females, however, did not differ among the different treatments. When the interval between two subsequent copulations of males is less than 1 h, males do not transfer a spermatophore during the second copulation. It is thus possible to produce artificially mated females with and without a spermatophore. However, the amount of sex pheromone released by mated females with and without a spermatophore did not differ. These results indicate that male-derived substances do not suppress release of sex pheromone by female S. rubrovittatus but, they may reduce their mating receptivity.